The Impact of COVID-19 Instigated Changes on Loneliness of Teachers and Motivation–Engagement of Students: A Psychological Analysis of Education Sector - Telyani, Abir El; Farmanesh, Panteha; Zargar, Pouya (Frontiers in Psychology, 2021)
Upon the spread of the global pandemic of COVID-19, education was transformed online in an abrupt manner. Amid this change, the education sector did not have room for proper decision-making and understanding of psychological effects. This theoretical analysis aims to contribute to the proposed Frontiers Research Topic, through (a) in-depth analysis of the pandemic status and behavioral psychology and (b) examining educational psychology from the perspective of teachers regarding sudden changes. As a result, implications are suggested based on interviews, linking to extant literature. The current research recognizes the difference between online learning and emergency remote education. While the former comprises prepared means of teaching and assessment, the latter is unaccompanied by such preparedness. Thus, there are variations in the outcomes of learning, motivation, and engagement. Scholars, teachers, deans, and educational managers can benefit from current results.